Novos aspectos no seguimento de carcinomas diferenciado e medular de tiroide - Yang, Ji Hoon [UNIFESP] (2015)
Artigo1: BACKGROUND: 18F-FDG PET/CT has emerged as a valuable tool in patients with high-risk differentiated thyroid cancer (DTC) by improving the identification of undifferentiated metastases, prediction of prognosis and management of clinical judgment. OBJECTIVE: To evaluate the clinical utility of 18F-FDG PET/CT in patients with high-risk DTC. METHODS: Single-center retrospective study with 74 patients with high-risk DTC, classified in 4 groups. Group 1: patients with positive sTg or TgAb, subdivided in Group 1A: negative RxWBS and no foci of metastases identified at conventional image (n=9); Group 1B: RxWBS not compatible with suspicious foci at conventional image or not proportional to sTg level (n=13); Group 2: patients with histological findings of aggressive DTC variants (n=21) and Group 3: patients with positive RxWBS (n=31). RESULTS: 18F-FDG PET/CT identified undifferentiated lesions and helped restage the disease in patients with refractory radioiodine metastases and those with aggressive disease. The scan helped guide clinical judgment in 9/13 (69%) patients of group 1B, 10/21 (48%) patients of group 2 and 2/31 (6%) patients of group 3. There was no clinical benefit associated with group 1A. 18F-FDG PET/CT was able to distinguish progressive from stable disease. CONCLUSION: 18F-FDG PET/CT is a useful tool in the follow-up of patients with high-risk DTC, mainly in the group of positive sTg or TgAb and negative RxWBS patients and in those with aggressive DTC variants. Additionally, this study showed that 18F-FDG PET/CT distinguished progressive from stable disease and helped display undifferentiated lesions guiding clinical assessments regarding surgeries or expectant treatments. Artigo2: Objective: Staging systems applied to medullary thyroid cancer (MTC) rely on initial clinical and pathological features and do not consider the response to treatment. To determine whether MTC staging can be improved by incorporating the first postoperative calcitonin measurement. Patients and measurements: Eighty-five patients being monitored for MTC (median follow-up 5 years) were retrospectively classified according to both the American Joint Committee on Cancer (AJCC) and the proposed combined risk stratification system (low, intermediate and high risk), which incorporates the first postoperative calcitonin measurement, using the outcomes no evidence of disease (NED), biochemical evidence of disease, structurally identifiable disease and death. Results: Ninety percent of AJCC I patients were classified as NED at final followup. When we added a postoperative calcitonin measurement, 95% low-risk patients were classified as NED at final follow-up. AJCC stages I and IV were associated, respectively, with no occurrence and a high rate (63%) of structurally identifiable disease. Stages II and III yielded similar predictions of structurally identifiable disease, 13% and 14%, respectively. When we included the postoperative calcitonin level, the patients with structural evidence of disease included none from the low-risk group, 10% from the intermediate group and 63% from the high-risk group. The proportion of variance explained analysis (PVE) was better for the combined risk stratification system (54%) than for the AJCC system alone (32%). Conclusion: Including the first postoperative calcitonin measurement with the anatomical staging system can better predict the clinical outcome of patients with MTC and refine the follow-up of these patients. Artigo3: Background: Calcitonin and CEA doubling times are established prognostic markers in medullary thyroid cancer (MTC). On the other hand, 18F-FDG PET/CT shows increasing detection rate with high blood tumor marker levels in several cancers. Thus, a higher rate of positive cases in MTC might be observed in patients with shorter calcitonin and CEA doubling times. Objective: To analyze the ability of 18F-FDG PET/CT in the determination of prognosis in the follow-up of patients with MTC. Material and Methods: Medical records of 17 patients with MTC who performed 18F-FDG PET/CT were analyzed retrospectively. All patients were classified into 2 groups: stable disease or progressive disease. Results: Eight patients presented progressive disease, and all showed 18F-FDG uptake (100%), compared to only three out nine patients who presented stable condition (33%). 18F-FDG PET/CT results were able to distinguish progressive from stable disease (p=0.009). Calcitonin levels higher than 4020 pg/mL (p=0.0004), CEA levels higher than 26.8 ng/mL (p=0.04) and calcitonin doubling time shorter than 24.1 months (p=0.015) were associated with progressive disease in our cohort. The proportion of variance explained analysis (PVE) that predicted progressive disease was, 32% for 18F-FDG uptake, 27.1% for calcitonin doubling time of 24.1 months and 41.2% for doubling time plus 18F-FDG PET/CT. Conclusion: 18F-FDG uptake was able to distinguish progressive from the stable disease. This tool should not replace the role of the validated calcitonin doubling time, but the combined information could improve the clinical reassessment and better provide identification of the risk group patients who deserves a more careful surveillance.